2019
DOI: 10.3892/ol.2019.11042
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential hub genes associated with the pathogenesis and prognosis of pancreatic duct adenocarcinoma using bioinformatics meta‑analysis of multi‑platform datasets

Abstract: Pancreatic duct adenocarcinoma (PDAC) is a highly malignant type of cancer with a low five-year survival rate. Gene alterations are crucial to the molecular pathogenesis of PDAC. Therefore, the present study analyzed gene expression profiles to reveal genes involved in the tumorigenesis of PDAC. A total of eight gene expression profiles (GSE15471, GSE16515, GSE41368, GSE62165, GSE62452, GSE71729, GSE71989 and GSE91035) and a PDAC dataset were acquired from the Gene Expression Omnibus and The Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…PLAU1 and MMP1 are associated with the extracellular matrix, cell-cell adhesion, and collagen catabolism in oral squamous carcinoma ( 25 ). PLAU1 and MMP1 play similar roles in malignant tumors and exhibit a high degree of connectivity ( 26 ). Moreover, PLAU1 was shown to promote disease progression through the secretion of matrix metalloproteinases (MMPs) ( 27 ), leading to localized matrix proteolysis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLAU1 and MMP1 are associated with the extracellular matrix, cell-cell adhesion, and collagen catabolism in oral squamous carcinoma ( 25 ). PLAU1 and MMP1 play similar roles in malignant tumors and exhibit a high degree of connectivity ( 26 ). Moreover, PLAU1 was shown to promote disease progression through the secretion of matrix metalloproteinases (MMPs) ( 27 ), leading to localized matrix proteolysis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAAD is a highly aggressive tumor with dismal prognoses which is resulted by the lack of reliable biomarkers and therapeutic targets [1]. In our exploration, we conducted comprehensive bioinformatics analyses to identify key genes related with the progression of PAAD and finally found three key genes as well as several potential small molecule drugs to treat PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, on the basis of big integrated data and bioinformatics, the promising key genes related with cancer development and prognosis can be identified with the widespread popularity of gene chips and the rapid development of high-throughput sequencing technology. Potential hub genes linked with the pathogenesis and outcome of PAAD were screened out using bioinformatics meta-analysis based on the GEO and TCGA databases [1]. Wu et al identified a nine-gene signature and established a prognostic nomogram used to predict the prognoses of PAAD patients [6].…”
mentioning
confidence: 99%
“…Moreover, fibronectin-induced EMT correlates with poor OS in surgically resected PC patients [89]. Currently, the use of multi-gene expression profile datasets and meta-analyses has led to the identification of fibronectin as one of ten hubs that may be involved in PC progression and pathogenesis [182]. Along these lines, focal adhesion kinase (FAK) activation downstream of integrin binding to fibronectin and collagens correlates with high levels of fibrosis and poor CD + cytotoxic T cell infiltration in PC; FAK inhibition limited tumor progression, markedly reduced tumor fibrosis, decreased the numbers of tumor-infiltrating immunosuppressive cells, and rendered the previously unresponsive KPC mouse model responsive to T cell immunotherapy and programmed cell death protein (PD)-1 antagonists.…”
Section: Fibronectinmentioning
confidence: 99%